2012
DOI: 10.3724/sp.j.1005.2012.00793
|View full text |Cite
|
Sign up to set email alerts
|

Advances in genome-wide association studies on essential hyperten-sion

Abstract: Since the first genome-wide association study was reported in 2007, hypertension has attracted numerous studies to identify its genetic basis. The first part of the current review summarizes the genetic loci associated with blood pressure/ hypertension identified by genome-wide association studies (GWAS) from January 2007 to September 2011, by race and chromosomal location. In the second part, we stress several important points in GWAS methodology, for example, selecting high-quality phenotypes and using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There is a large body of literature concerning essential hypertension and genetics. Padmanabhan et al found more than 100 single nucleotide polymorphisms (SNPs) and proved that these SNPs are associated with blood pressure regulation [5]. The method of the research is genome wide association studies, which allow us to suppose the function of genes by genome comparison and function net association.…”
Section: Theme 1: Essential Hypertension and Genetics Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of literature concerning essential hypertension and genetics. Padmanabhan et al found more than 100 single nucleotide polymorphisms (SNPs) and proved that these SNPs are associated with blood pressure regulation [5]. The method of the research is genome wide association studies, which allow us to suppose the function of genes by genome comparison and function net association.…”
Section: Theme 1: Essential Hypertension and Genetics Factorsmentioning
confidence: 99%
“…The two variants in the first question are the key issues. Xu et al (2012) showed some of the key variants in essential hypertension [4]. Their research tests the correlation between the existence of a variant and the SBP (systolic blood pressure) or DBP (diastolic blood pressure).…”
Section: Test For the Variantsmentioning
confidence: 99%
“…As technology has advanced, genome-wide association studies (GWASs) have gradually been applied to the analysis of complex diseases. A number of research institutes have conducted GWAS analyses of hypertension and have investigated the genetic etiology of hypertension at the level of whole genome (Xu and Yan, 2013). For example, the NPR3 gene encoding the natriuretic peptide receptor protein C has been demonstrated to be associated with the occurrence of hypertension in both European (International Consortium for Blood Pressure Genome-Wide Association Studies et al, 2011) and Asian populations (Kato et al, 2011) based on meta-analyses of GWASs.…”
Section: Introductionmentioning
confidence: 99%